ISSUES OF SPIRITUAL AND MORAL PERFECTION IN NAJMUDDIN KUBRA’S TEACHINGS - Sarvar Saidov (Western European Studies, 2025)
This article analyzes the contribution of the great Sufi master Najmuddin Kubra (1145–1221) to the development of Sufi thought on the basis of his treatise “Usul al-Ashara” (“The Ten Principles”). The study highlights the spiritual significance of each principle, their role in the process of human perfection, and the distinctive place of Najmuddin Kubra’s school in the history of Sufism. Through “Usul al-Ashara”, the inner laws of self-purification, the disciplining of the soul (nafs), and the attainment of stations of nearness to God are demonstrated. The article is devoted to a source-based and analytical exploration of these processes
Keywords: Najmuddin Kubra; Usul al-Ashara; Sufism